Cannabis against chronic musculoskeletal pain: a scoping review on users and their perceptions - Daniela Furrer; Edeltraut Kröger; Martine Marcotte; Nathalie Jauvin; Richard Bélanger; Mark Ware; Guillaume Foldes-Busque; Michèle Aubin; Pierre Pluye; Clermont E. Dionne (BMC, 2021)
Abstract Background Chronic musculoskeletal pain (CMP) may lead to reduced physical function and is the most common cause of chronic non-cancer pain. Currently, the pharmacotherapeutic options against CMP are limited and frequently consist of pain management with non-steroidal anti-inflammatories, gabapentinoids, or opioids, which carry major adverse effects. Although the effectiveness of medical cannabis (MC) for CMP still lacks solid evidence, several patients suffering from it are exploring this therapeutic option with their physicians. Objectives Little is known about patients' perceptions of their MC treatment for CMP. We aimed to increase this knowledge, useful for healthcare professionals and patients considering this treatment, by conducting a scoping literature review, following guidance by Arksey and O'Malley, to describe the views and perceptions of adult patients who had consumed MC to relieve chronic CMP. Methods Databases (PUBMED, EMBASE, Web of Science) and websites were searched using combinations of controlled and free vocabulary. All studies and study designs reporting on patients' perceptions regarding MC against CMP were considered. Studies had to include adult patients reporting qualitatively or quantitatively, i.e., through questionnaires, on MC use to treat CMP or other non-cancer pain, since studies reporting exclusively on perceptions regarding CMP were very rare. Study characteristics were extracted and limitations of the study quality were assessed. The review includes patients' demographic characteristics, patterns of MC use, perceived positive and negative effects, use of alcohol or other drugs, reported barriers to CM use, and funding sources of the studies. Results Participants of the 49 included studies reported that MC use helped them to reduce CMP and other chronic non-cancer pain, with only minor adverse effects, and some reported improved psychological well-being. In the included studies, men represent between 18 and 88% of the subjects. The mean age of participants in these studies (42/49) varied between 28.4 and 62.8 years old. The most common route of administration is inhalation. Conclusion MC users suffering from CMP or other chronic non-cancer pain perceived more benefits than harms. However, the information from these studies has several methodological limitations and results are exploratory. These user-reported experiences must thus be examined by well-designed and methodologically sound clinical or observational studies, particularly regarding CMP, where reports are very scarce.